2019
DOI: 10.3390/s19102218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Validating Emotion Elicitation Using English and Arabic Movie Clips on a Saudi Sample

Abstract: With the advancement of technology in both hardware and software, estimating human affective states has become possible. Currently, movie clips are used as they are a widely-accepted method of eliciting emotions in a replicable way. However, cultural differences might influence the effectiveness of some video clips to elicit the target emotions. In this paper, we describe several sensors and techniques to measure, validate and investigate the relationship between cultural acceptance and eliciting universal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 100 publications
(158 reference statements)
0
11
0
Order By: Relevance
“…In Saudi society, showing weak emotions is uncommon for Arab men. Alghowinem, Goecke, Wagner, and Alwabil (2019) reported that women were found to be emotionally expressive, whereas men manifested strong emotions.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi society, showing weak emotions is uncommon for Arab men. Alghowinem, Goecke, Wagner, and Alwabil (2019) reported that women were found to be emotionally expressive, whereas men manifested strong emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion monitoring was proposed for healthcare using a low cost wearable EEG headset [ 71 ]. Moreover, effect of culture on emotion recognition was investigated using EEG signals by presenting video clips in two different languages [ 72 ]. A feature extraction method was proposed to improve emotion recognition accuracy using EEG signals [ 73 ].…”
Section: Related Workmentioning
confidence: 99%
“…Facial expressions of emotions have a complex role in social interactions, and they are crucial for communication, connection, and building rapport with others ( Schmidt & Cohn, 2001 ; Parkinson, 2005 ). Indeed, recent work evaluating importance of cultural specificity of emotional film clips reported that stimuli depicting the participants’ own culture provoked stronger facial affective responses than non-culturally specific stimuli ( Alghowinem et al, 2019 ). However, similar effects were not observed in the self-reported emotion ratings ( Alghowinem et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent work evaluating importance of cultural specificity of emotional film clips reported that stimuli depicting the participants’ own culture provoked stronger facial affective responses than non-culturally specific stimuli ( Alghowinem et al, 2019 ). However, similar effects were not observed in the self-reported emotion ratings ( Alghowinem et al, 2019 ). Thus, there is interest in developing paradigms that could be used to assess how evoked facial affect might change as the illness progresses or following an intervention.…”
Section: Introductionmentioning
confidence: 99%